School Type, Lifestyle Factors and the Risk of Metabolic Syndrome in Nigerian Adolescents (Global Journal of Science Frontier Research, 2020)
Abstract not found
Keywords: metabolic syndrome; school health; adolescents; socioeconomic status; health promotion